Two new species of Neotraginops Prado from Costa Rica and Brazil (Diptera: Odiniidae: Traginopinae) - Flores, Heloísa Fernandes; Pirani, Gabriela; Gaimari, Stephen D.; de Souza Amorim, Dalton (Zootaxa, 2021)
Two new species of Neotraginops Prado (Neotraginops fachini sp. nov. and Neotraginops arikemi sp. nov.) are added to the known Neotropical diversity of the Traginopinae (Odiniidae), and the range is expanded for Neotraginops mexicanus Hernández-Ortiz & Dzul-Cauich. A key to the species of the genus is provided. Along with descriptions, photographs and detailed illustrations of the male terminalia are included for the new species.